Photodiode based on Pb0.9Cd0.1S ternary alloy semiconductor for solar tracking systems - Wageh, S.; Karabulut, Abdulkerim; Dere, A.; Al-Sehemi, Abdullah G.; Al-Ghamdi, Ahmed A.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Springer, 2018)
The fabrication and photoelectrical properties of the photodiodes based on the ternary alloy of semiconductor nanocrystallite Pb0.9Cd0.1S with coumarin dopant were investigated. The structure, stability, melting temperature and optical bandgap of the prepared nanostructure were characterized by X-ray diffraction, thermogravimetric analysis, Infrared, Raman spectroscopy and UV-VIS-NIR spectroscopies. The characterization of the ternary alloy indicates that the crystal structure of the ternary alloy is cubic with some distortion in (111) direction and has a nanosize of 9 nm. The photoelectrical characteristics of fabricated Si-based photodiodes with coumarin doped PbCdS interfacial layers were investigated by using current-voltage, transient photocurrent and capacitance/conductance-voltage measurements. Some electrical parameters and the effects of illumination on these parameters have been determined from these measurements. Consequently, results of experiments suggest that the ternary alloy Pb0.9Cd0.1S nanocrystallite based photodiode can be suitable for optoelectronic applications.
Keywords: Schottky Diode; Optical-Properties; Interface; Films; Pbs; Parameters